Shareholders Should Welcome Employees as Directors - Margit Osterloh; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2004)
The most influential theory of corporate governance, principal agency theory, does not take into consideration that the key task of modern corporations is to generate and transfer firm-specific knowledge. It proposes that, in order to overcome the widespread corporate scandals, the interests of top management and directors should be increasingly aligned to shareholder interests by making the board more responsible to shareholders, and strengthening the monitoring of top management by independent outside directors. Corporate governance reform needs to go in another direction altogether. Firm-specific knowledge investments are, like financial investments, not ex ante contractible, leaving investors open to exploitation by shareholders. Employees therefore refuse to make firm-specific investments. To gain a sustainable competitive advantage, there must be an incentive to undertake such firm-specific investments. Three proposals are advanced to deal with this conflict: (1) The board should rely more on insiders. (2) The insiders should be elected by those employees of the firm making firm-specific knowledge investments. (3) The board should be chaired by a neutral person. These proposals have major advantages: they provide incentives for knowledge investors; they countervail the dominance of executives; they encourage intrinsic work motivation and loyalty to the firm by strengthening distributive and procedural justice, and they ensure diversity on the board while lowering transaction costs. These proposals for reforming the board may help to overcome the crisis corporate governance is in. At the same time, they connect agency theory with the knowledge-based theory of the firm.
Keywords: 330; conflict management; corporate governance; agency theory; firm-specific investment; knowledge capital